Examining and evaluating multilevel communication within a mixed-methods, community-based participatory research project in a rural, minority–majority U.S. Town. Issue 2 (4th March 2021) - Palmer-Wackerly, Angela L.; Reyes, Maria S.; Ali, Sahra H.; Gocchi Carrasco, Kim; Habecker, Patrick; Houska, Kristen; Chaidez, Virginia; Soliz, Jordan; Tippens, Julie A.; Holland, Kathryn J.; Pytlik Zillig, Lisa; Patterson, Kali; et al.
ABSTRACT: Community-based participatory research (CBPR) has been shown to improve health and social well-being by including diverse, marginalized community voices within academic–community partnerships. Although CBPR has gained in popularity, an explicit examination and evaluation of communication processes and outcomes throughout an entire CBPR project is lacking. Here, we analyze interviews with 10 stakeholders (i.e. 4 academic and 6 community partners) about their experiences in a three-phase, mixed-methods project exploring Hispanic and Somali community members' perceptions of healthcare needs and access in a rural U.S. community. Results reflect that CBPR endeavors include communication challenges, successes, and ongoing tensions not simply between the academic group and community partners but also within these groups. We encourage academic–community research partners to devote considerable efforts to strengthening effective communication between and within multiple identity groups throughout an entire CBPR project (including evaluation) as they work to create, complete, and sustain project goals and outcomes.